A Cu(i)–I coordination polymer fluorescent chemosensor with amino-rich sites for nitro aromatic compound (NAC) detection in water. Issue 34 (19th August 2020) - Zhang, Yu; Yang, Qingfeng; Li, Xiaoping; Miao, Chengxia; Hou, Qin; Ai, Shiyun
Abstract : The detection sensitivity increased as the sizes of [Cu2 I2 (MA)2 ] decreased and the selectivity improved by introducing amino-rich ligands. Abstract : A fluorescent coordination polymer with formula [Cu2 I2 (MA)2 ] (MA = melamine) (1 ) was prepared via a solvothermal method. The nanometer size of 1 was obtained by the nanoprecipitation method. Compound 1 features a 1-D double [Cu2 I2 ] chain anchoring the MA molecules on both sides of the chain with uncoordinated amino and heterocyclic nitrogen groups as recognition sites to interact with guest molecules. Compound 1 exhibits excellent thermal stability and is also stable in acidic and basic media. As a fluorescent sensor, compound 1 was successfully used for the detection of NACs such as 2, 4, 6-trinitrophenol (TNP), nitrobenzene (NB), p -nitrophenol (4-NP), 2, 4-dinitrotoluene (2, 4-DNT), and 2, 4-dinitrophenol (2, 4-DNP) in aqueous media by fluorescence quenching. The quenching sequence is TNP > 2, 4-DNP > 2, 4-DNT > 4-NP > NB. Furthermore, the sensing sensitivity increased as the particle size of 1 decreased. The limit of detection for TNP is 0.717 μM. We also discuss the probable quenching mechanism based on the theoretical calculations and UV-vis absorption spectroscopy.